Estudo sobre quantificação relativa de bactérias do biofilme lingual de crianças sob ventilação mecânica invasiva - MONTEIRO, Tania Mara Lopes Ortiz (2024)
The lingual biofilm of patients admitted to the Intensive Care Unit (ICU) under invasive mechanical ventilation (IMV) can harbor respiratory pathogens, enabling bacterial translocation from the oral environment to the lungs via the orotracheal tube, causing serious systemic infections, such as Mechanical Ventilation-Associated Pneumonia (MVAP), with repercussions on hospitalization days and days on IMV. Colonization of the lingual biofilm by pathogens occurs 48 hours after the patient is intubated, and may be related to inadequate oral hygiene. The microorganisms involved include gram-negative bacteria such as Pseudomonas aeruginosa and Klebsiella pneumonia. The multiplication of these pathogens occurs due to the failure of the IMV patient's defense system, so that patients infected with these multidrug-resistant pathogens have the worst outcomes with the highest mortality. Studies have shown that the implementation of an Oral Hygiene Protocol is an effective tool in reducing the relative quantification of bacteria in the lingual biofilm of children intubated in the ICU and in significantly reducing the number of days of invasive mechanical ventilation. Thus, the hypothesis of this thesis is that the multiplication of total bacteria in the lingual biofilm of children under invasive mechanical ventilation and the frequency of the pathogens Pseudomonas aeruginosa and Klebsiella pneumoniae in this lingual biofilm may vary according to hospital outcomes, oral hygiene, the presence of VAP, days of hospitalization and days under IMV in a paediatric ICU. Chapter I of this thesis was the original article "Relative quantification of Pseudomonas aeruginosa and Kleibsiela pneumoniae in the lingual biofilm of children under invasive mechanical ventilation and its association with hospital outcome in an Intensive Care Unit", which aimed to investigate the association between the quantity of pathogens Pseudomonas aeruginosa and Klebsiella pneumoniae in the lingual biofilm of children under invasive mechanical ventilation and hospital outcome (discharge and death) in a Pediatric ICU. This is a cohort study of 24 IMV patients of both sexes aged between 1 and 144 months. Tongue biofilm was collected at the time of intubation (T1) and 48 hours after the first collection (T2). DNA was extracted from the samples and a bacterial primer pair for Pseudomonas aeruginosa and a bacterial primer pair for Klebsiella pneumoniae were used to detect the DNA of the specific bacteria. Real-time qPCR (Polymerase Chain Reaction) allowed the relative quantification of the bacteria detected and amplified in each cycle of the reaction. The Ct (threshold cycle) curve indicates the fractional cycle number at which the amount of amplified target reaches a fixed threshold. Ct levels are inversely proportional to the amount of target nucleic acid in the sample (i.e. the lower the Ct level, the higher the amount of nucleic acid). The ∆Ct (delta Ct) consists of the difference in expression between the target and control sample (average of Pseudomonas aeruginosas or Klebsiella pneumoniae - average of the 16S universal bacterial primer), with a positive ∆Ct indicating fewer bacteria and a negative ∆Ct indicating more bacteria. The results were analyzed using the qPCR data quantification method, ∆∆Ct (delta delta Ct), which is the difference between ∆CtT2 and ∆CtT1, resulting in the quantitative variation of bacteria in each sample. When testing the association between the presence of the pathogens evaluated at the study times and the presence or absence of clinical signs of lingual biofilm, no significant associations were observed. The association between the presence of the pathogens Pseudomonas aeruginosa and Klebsiella pneumoniae in the lingual biofilm of children under IMV with hospital discharge (15 patients) and death (9 patients) within the T1 and T2 study times revealed that in T2, the percentage of Pseudomonas aeruginosa present in the lingual biofilm of patients who died was statistically higher than in patients who were discharged (90% versus 10%; P = 0.033). When analyzing the amount of pathogens in the lingual biofilm of children under IMV, no significant differences were identified between the discharge and death groups, since the amount of bacteria (Pseudomonas aeruginosas and Klebsiella pneumoniae) did not vary in relation to the hospital outcome. Multivariate logistic regression of the association between the presence of pathogens in the lingual biofilm of intubated children, adjusted for age and time under IMV and the occurrence of death, reinforced that the presence of Pseudomonas aeruginosa in the lingual biofilm at T2 was associated with the outcome of death even after adjusting for other confounding factors (adjusted OR = 39.2%; 95%CI = 1.07-1485; P = 0.048). Conclusion: The presence of Pseudomonas aeruginosa in the lingual biofilm of children under IMV seems to be more important than its quantity for the association with death in the pediatric ICU. Practical implications: Contributions to health care, highlighting the importance of studies focused on the bacterial presence in the lingual biofilm of children under IMV in Pediatric ICUs in order to draw up public health strategies aimed at its control. Chapter II of this thesis was the article "Relative quantification of total bacteria in the lingual biofilm of children intubated in an Intensive Care Unit, oral hygiene, hospital outcome, days of hospitalization, days under invasive mechanical ventilation and Mechanical Ventilation-Associated Pneumonia: is there an association?" with the aim of investigating whether there is an association between the relative quantification of total bacteria in the lingual biofilm of children intubated in the ICU, oral hygiene, hospital outcome, days of hospitalization, days on Invasive Mechanical Ventilation and Mechanical Ventilation-Associated Pneumonia. This is a cohort study of 24 patients on IMV, both sexes and aged between 1 and 144 months. Tongue biofilm was collected at the time of intubation (T1) and 48 hours after the first collection (T2). DNA was extracted from the samples and a 16S universal bacterial primer pair was used to detect the DNA of the total bacteria present in the sample. Real-time qPCR (Polymerase Chain Reaction) allowed the relative quantification of the bacteria detected and amplified in each cycle of the reaction. The Ct (threshold cycle) curve indicates the fractional cycle number at which the amount of amplified target reaches a fixed threshold. Ct levels are inversely proportional to the amount of target nucleic acid in the sample (i.e. the lower the Ct level, the greater the amount of nucleic acid/more bacteria). The ∆Ct (delta Ct) consists of the difference in expression between the target and control sample (Mean CtT2 - Mean CtT1), with a positive ∆Ct indicating fewer bacteria and a negative ∆Ct indicating more bacteria. ∆∆Ct (delta delta Ct) is the difference between ∆CtT2 and ∆CtT1, resulting in the quantitative variation of bacteria in each sample. The results were analyzed using the qPCR data quantification method, the Ct method, and it can be seen that in the biofilm collected, the mean Ct for relative quantification of lingual biofilm bacteria was lower (25.15±6, 17) in T1 (lower Ct=more bacteria) while the mean was higher (27.23±5.61) in T2 (higher Ct=less bacteria) (paired t-test, p= 0.0394), revealing a significant decrease in the quantification of pathogens in the lingual biofilm after the Oral Hygiene Protocol (OHP) was implemented. The average amount of total bacteria in the lingual biofilm of the total study sample was divided according to the outcome of hospitalization (discharge and death), using relative quantification using the ∆∆Ct method. There was a lower relative expression of total bacteria in the children who were discharged (73,093) than those who died (114,380), revealing a tendency for the latter to have greater colonization of total bacteria in the lingual biofilm, although there was no significant difference between the groups (p>0.05, Mann-Whitney test). The results showed a negative (inverse) correlation between ∆Ct and the number of days of hospitalization (r = -0.279; P = 0.185), but no statistical difference. As well as a statistical difference in the negative correlation between ∆Ct and number of days in IMV (r = -0.422 and p= 0.040), with moderate magnitude and a coefficient of determination (r2) of 0.178, revealing that the greater number of participants (∆Ct positive=fewer bacteria) with greater control of the lingual biofilm spent less time in IMV, with a shared variance of 17.8%. Multiple regression analysis was performed to estimate the effect of ∆Ct, adjusted for age, on days of hospitalization and days in IMV. There was no significant difference between ∆Ct and days of hospitalization and the analysis adjusted for age showed a borderline statistical measure (coefficient = -0.41, P = 0.053) for the relationship between ∆Ct and days in IMV, indicating that there was not enough strong evidence to prove the association. Conclusion: The implementation of an Oral Hygiene Protocol proved to be an effective tool in reducing the quantification of total bacteria in the lingual biofilm of children intubated in an Intensive Care Unit, with a lower relative quantification of total bacteria in the lingual biofilm of children who were discharged and a tendency for those who died to show greater colonization of total bacteria in this biofilm. Participants with greater control of lingual biofilm (∆Ct positive=fewer bacteria) spent less time on Invasive Mechanical Ventilation. Thus, these patients benefit more when the Oral Hygiene Protocol is used. However, in this study, it was not possible to observe a strong association with days of hospitalization. Practical implications: Contributions to health care, highlighting the importance of developing and implementing a PHB in a Pediatric ICU in order to reduce the relative quantification of lingual biofilm bacteria of intubated children and reduce days on invasive mechanical ventilation.